2014
DOI: 10.4236/abc.2014.43025
|View full text |Cite
|
Sign up to set email alerts
|

4,4’-Methylenebis(2-chloroaniline) (MBOCA) May Be Highly Toxic and a Carcinogen Based on an Experimental Study with Mice

Abstract: Abstract4,4'-Methylenebis(2-chloroaniline) (MBOCA) is a probable human carcinogen. Few studies have been performed regarding the genotoxicity of MBCOA, and the MBOCA metabolic pathway is not fully understood. We treated four-week-old ICR male mice weighing 25 -30 g with MBOCA and observed the effects of MBOCA on the internal organs. It can be concluded that MBOCA is a carcinogen and also affects gene regulation. Oral or topical administration of 50 mg/kg, 100 mg/kg or 200 mg/kg MBOCA resulted in 56% -81% of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The highest risk of exposure to MBOCA is in workers who absorb MBOCA vapor or dusts through the skin, or inhale MBOC dusts (Chen et al, 2014). Findings from studies have shown that moderate and chronic exposure to MBOCA can cause bladder tumors (Chen et al, 2014;Kiriluk et al, 2012;Lin et al, 2013).…”
Section: -2 44′-methylene-bis(2-chloroaniline) (Mboca)mentioning
confidence: 99%
“…The highest risk of exposure to MBOCA is in workers who absorb MBOCA vapor or dusts through the skin, or inhale MBOC dusts (Chen et al, 2014). Findings from studies have shown that moderate and chronic exposure to MBOCA can cause bladder tumors (Chen et al, 2014;Kiriluk et al, 2012;Lin et al, 2013).…”
Section: -2 44′-methylene-bis(2-chloroaniline) (Mboca)mentioning
confidence: 99%